1995
DOI: 10.1161/01.hyp.25.6.1224
|View full text |Cite
|
Sign up to set email alerts
|

α-Adrenoceptor Modulation of Norepinephrine and ATP Release in Isolated Kidneys of Spontaneously Hypertensive Rats

Abstract: The present study investigates sympathetic cotransmission and its alpha-adrenoceptor-mediated modulation in kidneys of spontaneously hypertensive rats (SHR, 12 to 14 weeks) and age-matched normotensive Wistar-Kyoto rats (WKY). In the presence of cocaine and corticosterone, renal nerve stimulation at 1 Hz (30 seconds) induced a greater outflow of norepinephrine in SHR (4.2 +/- 0.2 pmol/g kidney) than in WKY (3.0 +/- 0.2 pmol/g kidney). The alpha 2-adrenoceptor antagonist rauwolscine (0.01 to 1 mumol/L) increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 43 publications
1
39
1
Order By: Relevance
“…39 Negative feedback systems should modulate this hyperactivity through the stimulation of presynaptic ␣ 2 -adrenergic and DD2 receptors. 12,42 In the spontaneously hypertensive rat (SHR), the *Gender was eliminated as an independent predictive factor for SBP. †Age was eliminated as a independent predictive factor for both SFT measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Negative feedback systems should modulate this hyperactivity through the stimulation of presynaptic ␣ 2 -adrenergic and DD2 receptors. 12,42 In the spontaneously hypertensive rat (SHR), the *Gender was eliminated as an independent predictive factor for SBP. †Age was eliminated as a independent predictive factor for both SFT measurements.…”
Section: Discussionmentioning
confidence: 99%
“…42 However, the ability of dopamine to stimulate the DD2R and hence inhibit the release of norepinephrine has been shown to be impaired, 43 leading to increased norepinephrine-mediated vasoconstriction. Furthermore, the replacement of a section of chromosome 8 from the SHR that carries the DD2R gene with that from the normotensive Brown-Norway rat reduced blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…43 There is an increased ␣ 2 -adrenoceptor-mediated autoregulation of NE release in SHR kidneys caused by increased intrasynaptic NE. 44 The increase in SNS activity in SHR and SHR/y animals also could be reflected in changes in gene expression that occur through receptor-mediated events involving both NE and its effect on other hormones. It has been proposed that angiotensin II interacts with the SNS to facilitate NE release in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…10 Extracellular ATP exerts a substantial influence on hemodynamic function, acting via P2 purinoceptors, on a variety of tissues and organs, [2][3][4][5] including the kidney. 4,5,[11][12][13][14][15] A growing body of evidence obtained in both dogs and rats supports the hypothesis that extracellular ATP exerts a role in mediating renal autoregulatory vascular resistance responses, 14 -18 which are caused by active adjustments of vascular smooth muscle tone, primarily in the afferent arterioles. 14,15 Studies using the isolated blood-perfused juxtamedullary nephron preparation demonstrated that ATP, superfused over the renal microvessels, exerts selective afferent arteriolar vasoconstriction without affecting efferent arteriolar tone, 19,20 which is an important criterion for the agent mediating autoregulatory behavior.…”
mentioning
confidence: 99%